2022
DOI: 10.1177/1097184x211064321
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchies of Masculinity and Lad Culture on Campus: “Bad Guys”, “Good Guys”, and Complicit Men

Abstract: Research on ‘lad culture’ and gender-based violence (GBV) in student communities has examined ‘hypermasculine’ gender performances, with little attention paid to hierarchies of masculinity. We explore ‘lad culture’ by analysing qualitative, in-depth interviews with students. Our findings challenge simplistic constructions of ‘good guys’ as allies/protectors in opposition to hypermasculinised, deviant ‘bad guys’. We demonstrate how such binary constructions are premised upon gendered norms of men-as-protectors/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…The potential implication is that it is these 'bad guys' who need to be the target of gender justice interventions, not the 'good guys'. Fundamentally, we agree with others (Carline et al, 2018;Jordan et al, 2022) that the best way to anticipate and engage with these complexities is through interactive sessions (within bystander programmes and beyond) with male peer groups where real conversations and 'disruptive moments' can take place (Jordan et al, 2022: 715).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The potential implication is that it is these 'bad guys' who need to be the target of gender justice interventions, not the 'good guys'. Fundamentally, we agree with others (Carline et al, 2018;Jordan et al, 2022) that the best way to anticipate and engage with these complexities is through interactive sessions (within bystander programmes and beyond) with male peer groups where real conversations and 'disruptive moments' can take place (Jordan et al, 2022: 715).…”
Section: Discussionsupporting
confidence: 62%
“…This is because meaningful change requires an examination of the inevitably discomforting behaviours and emotions underpinning boys' and men's complicities in gender injustice (Keddie, 2021). Relatedly, there is a tendency for those men who draw on notions of the 'protecter mindset' -as referenced by Sorcha for example -to construct themselves as the 'good guys' in opposition to the 'bad guys' who sexually violate women (Carline et al, 2018;Jordan et al, 2022). The potential implication is that it is these 'bad guys' who need to be the target of gender justice interventions, not the 'good guys'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this may relate to prevailing gender norms in which men identify with the role of “protector”. (21) Defending honour and asserting dominance over others may increase men’s resistance in the face of conflict, in turn increasing the risk of fatal outcomes. This was shown in a recent South African study of co-occurring violence during robbery events in which male victims were significantly more at risk of a fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…South African data have consistently shown that men are not only the main perpetrators of violence, [5] they also have an overwhelmingly higher risk of violent death. Part of this may relate to prevailing gender norms in which men identify with the role of "protector" [21]. Defending honour and asserting dominance over others may increase men's resistance in the face of conflict, in turn increasing the risk of fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%